Rare diseases and orphan drugs: 500 years ago. Issue 1 (December 2015) - Dooms, Marc
Abstract In 1581 Rembert Dodoens wrote "Medicinalium observationum exempla rara, recognita et aucta" a Latin book about the diagnosis and treatment of disorders with a low prevalence.